Double threshold in bi- and multilingual contexts: preconditions for higher academic attainment in English as an additional language - Lechner, Simone; Siemund, Peter (Frontiers in Psychology, 2014)
Bi- and multilingualism has been shown to have positive effects on the attainment of third and additional lan-guages. These effects, however, depend on the type of bi- and multilingualism and the status of the languages involved (Cenoz 2003; Jessner 2006). In this explorative trend study, we revisit Cummins’ Threshold Hypothesis (1979), claiming that bilingual children must reach certain levels of attainment in order to a) avoid academic deficits and b) allow bilingualism to have a positive effect on their cognitive development and academic attain-ment. To this end, we examine the attainment of English as an academic language of 16-year-old school children from Hamburg (n=52). Our findings support the existence of thresholds for literacy attainment. We argue that language external factors may override positive effects of bilingualism. In addition, these factors may compensate negative effects attributable to low literacy attainment in German and the heritage languages. We also show that low attainment levels in migrant children’s heritage languages preempt high literacy attainment in additional languages.